2018
DOI: 10.1002/jsfa.9195
|View full text |Cite
|
Sign up to set email alerts
|

Foliar antitranspirant and soil superabsorbent hydrogel affect photosynthetic gas exchange and water use efficiency of maize grown under low rainfall conditions

Abstract: Soil SAP and foliar FA use under low rainfall conditions had little influence on crop water consumption but improved plant WUE by enhancing photosynthesis and increasing kernel number. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 46 publications
(105 reference statements)
1
22
0
Order By: Relevance
“…The Chl (a+b) content under both moisture conditions did not significantly change when FA was applied alone (Figure 3). Few studies show that foliar FA spraying has little effect on Chl (a+b) content (Goreta et al, 2007;Celik et al, 2010;Yang et al, 2019). However, Anjum et al (2011) demonstrated that Chl (a+b) in maize plants significantly improves by FA spraying under WD and WW conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The Chl (a+b) content under both moisture conditions did not significantly change when FA was applied alone (Figure 3). Few studies show that foliar FA spraying has little effect on Chl (a+b) content (Goreta et al, 2007;Celik et al, 2010;Yang et al, 2019). However, Anjum et al (2011) demonstrated that Chl (a+b) in maize plants significantly improves by FA spraying under WD and WW conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Super absorbent polymers have been widely used in agricultural and forest soil to increase moisture conditions and promote the growth of crops and trees [14,15,[39][40][41]. Our study showed that C. formosanus may be attracted by super absorbent polymers placed around plant roots.…”
Section: Discussionmentioning
confidence: 68%
“…Under the normal conditions of agroecosystems, water shortage would limit crop growth, while excessive use of water would increase production costs and even pollute the environment due to enhanced fertilizer leaching. [1][2][3] Hereby, the improvement of agricultural water use efficiency is becoming a key approach to reduce irrigation water consumption, mitigate water shortage and reduce environmental problems. In order to achieve these goals in the eld of agriculture, hydrogels are deemed to be a potential candidate because of their water-adsorbing capacity and slowrelease function by virtue of their elastic networks.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] In contrast, most of them are subject to serious limitations such as a relatively low photothermal conversion efficiency, limited absorption range, which remains a practice challenge for agriculture applications. Alternatively, detonation nanodiamond (DND) formed by an sp 3 -carbon diamond core and a reconstructed sp 2 -carbon surface layer have recently received great attention on account of their inherent features, including high biocompatibility, large surface area, high thermal conductivity, spherical morphology, and surface functionality. [24][25][26] In additionally, DND is an excellent photothermal material with an absorption range spanning across the UV, visible and even near-infrared regions.…”
Section: Introductionmentioning
confidence: 99%